Comparative Study on Copyright Exception for Teaching Purposes: Australia, Malaysia and the United Kingdom (Journal of International Studies, 2020)
While education is considered a basic human right, the copyright system however seems to hamper public access to information and knowledge. This is especially so when information that largely comes from developed countries are used as commodities that have to be bought by developing countries. This paper compares the international and national laws in Malaysia, United Kingdom and Australia on the copyright exceptions to materials used for teaching purposes. It analyzes the different ways countries manage and balance between copyright owners and copyright users’ interest and shows that in many circumstances, copyright owners are over-protected by national copyright systems although this is not required by international copyright law. This paper also shows that international treaties governing copyright law do allow some flexibility for member countries to implement copyright systems based on their own needs and circumstances but such opportunity is not fully utilized by member countries for the benefit of the public.